A multiwavelength study of the dual nuclei in Mrk 212. Issue 3 (30th October 2020) - Rubinur, K; Kharb, P; Das, M; Rahna, P T; Honey, M; Paswan, A; Vaddi, S; Murthy, J
ABSTRACT: We present radio observations of the galaxy merger remnant Mrk 212 with the Karl G. Jansky Very Large Array (VLA) and the upgraded Giant Meter Radio Telescope (uGMRT). Mrk 212 has two previously known radio sources associated with the two optical nuclei, S1 and S2, with a projected separation of ∼6 kpc, making it a dual active galactic nuclei (AGN) candidate. Our new 15-GHz VLA observations reveal that S1 is a double radio source centred around the optical nucleus; its total extent is ∼750 pc its average 1.4−8.5 GHz spectral index is −0.81 ± 0.06. S1 therefore resembles a compact symmetric object. The 15-GHz VLA image identifies the radio source at S2 to be a compact core. Our radio observations therefore strongly support the presence of a dual AGN in Mrk 212. The optical emission line flux ratios obtained from the Himalayan Chandra Telescope (HCT) observations however, show that S1 and S2 both fall in the AGN + star formation (SF) region of the Baldwin, Philips and Terlevich (BPT) diagram. Weak AGN lying in the SF or AGN + SF intermediate regions in the BPT diagram have indeed been reported in the literature; our sources clearly fall in the same category. We find an extended radio structure in our newly reduced 8.5-GHz-VLA data, that is offset by ∼1 arcsec from the optical nucleus S2. New deep FUV and NUV observations with the Ultraviolet Imaging Telescope aboard AstroSat reveal SF knots around S2 as well as kpc-scale tidal tails; the SF knots around S2 coincide with the extended radio structure detected at 8.5 GHz. The radio spectral indices are consistent with SF. Any possible association with the AGN in S2 is unclear at this stage.